2008
DOI: 10.1038/sj.bjc.6604264
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of ispinesib, a kinesin spindle protein inhibitor, with docetaxel in patients with advanced solid tumours

Abstract: The aim of this study is to define the maximum tolerated dose (MTD), safety, pharmacokinetics (PKs) and efficacy of ispinesib (SB-715992) in combination with docetaxel. Patients with advanced solid tumours were treated with ispinesib (6 -12 mg m À2 ) and docetaxel (50 -75 mg m À2 ). Docetaxel was administered over 1 h followed by a 1-h infusion of ispinesib on day 1 of a 21-day schedule. At least three patients were treated at each dose level. Blood samples were collected during cycle 1 for PK analysis. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…An explanation for the clinical failure of mitosis-specific suppressors is the much smaller proportion of mitotic cells in human tumors compared with the animal xenograft models (26). Because of the insufficient antitumor effect of monotherapy, several ongoing clinical studies have incorporated KIF inhibitors with chemotherapeutic agents including carboplatin, capecitabine, and docetaxel to explore potential synergistic effects (27). In addition, drug resistance continues to be a major challenge in HCC chemotherapy (8).…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for the clinical failure of mitosis-specific suppressors is the much smaller proportion of mitotic cells in human tumors compared with the animal xenograft models (26). Because of the insufficient antitumor effect of monotherapy, several ongoing clinical studies have incorporated KIF inhibitors with chemotherapeutic agents including carboplatin, capecitabine, and docetaxel to explore potential synergistic effects (27). In addition, drug resistance continues to be a major challenge in HCC chemotherapy (8).…”
Section: Discussionmentioning
confidence: 99%
“…The first kinesin inhibitor to be developed was monastrol, which targets KIF11 [31], and several new inhibitors are currently under development [32][33][34][35][36]. For example, HR22C16, which is also a KIF11 inhibitor, targets taxol-sensitive and -resistant ovarian cancer cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…(61) Presently, this quinazolinone derivative represents the most studied Eg5 inhibitor and is now in a phase II clinical trial. (62)(63)(64)(65) The phase I studies for solid tumors indicated ispinesib is well tolerated with an acceptable safety profile and no indications of neurotoxicity. (62) However, recent results from the phase II trial in 15 patients with metastatic hepatocellular carcinoma showed no conclusive evidence of benefit with ispinesib monotherapy.…”
Section: Involvement Of Kif In Taxane Resistancementioning
confidence: 99%
“…(62)(63)(64)(65) The phase I studies for solid tumors indicated ispinesib is well tolerated with an acceptable safety profile and no indications of neurotoxicity. (62) However, recent results from the phase II trial in 15 patients with metastatic hepatocellular carcinoma showed no conclusive evidence of benefit with ispinesib monotherapy. (63) Other results of ispinesib from recurrent or metastatic squamous cell carcinoma of the head and neck, melanoma, colorectal cancer, ovarian cancer and renal cell carcinoma are similar in suggesting a lack of clinical efficacy.…”
Section: Involvement Of Kif In Taxane Resistancementioning
confidence: 99%